2013
DOI: 10.1186/1471-2261-13-52
|View full text |Cite
|
Sign up to set email alerts
|

Beta-blockers for the prevention of sudden cardiac death in heart failure patients: a meta-analysis of randomized controlled trials

Abstract: BackgroundIn many studies, beta-blockers have been shown to decrease sudden cardiac death (SCD) in heart failure patients; other studies reported mixed results. Recently, several large randomized control trials of beta blockers have been carried out. It became necessary to conduct a systematic review to provide an up-to-date synthesis of available data.MethodsWe conducted a meta-analysis of all randomized controlled trials examining the use of beta-blockers vs. placebo/control for the prevention of SCD in hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(77 citation statements)
references
References 43 publications
(34 reference statements)
1
73
0
3
Order By: Relevance
“…This was consistent with other research that concluded in patients with CHD who underwent noncardiac surgery, beta-blockers can reduce the incidence of death and MACE significantly, especially in patients who have recently experienced a myocardial infarction and patients with heart failure [33]. Beta-blocker therapy in heart failure patients also proven to reduce the risk of sudden death from a cardiovascular event by 31%, 29% cardiovascular death and death from all causes by 33% [34].…”
Section: Discussionsupporting
confidence: 91%
“…This was consistent with other research that concluded in patients with CHD who underwent noncardiac surgery, beta-blockers can reduce the incidence of death and MACE significantly, especially in patients who have recently experienced a myocardial infarction and patients with heart failure [33]. Beta-blocker therapy in heart failure patients also proven to reduce the risk of sudden death from a cardiovascular event by 31%, 29% cardiovascular death and death from all causes by 33% [34].…”
Section: Discussionsupporting
confidence: 91%
“…Nonetheless, our study corroborates a potential reduction in mortality with CIs from propensity-adjusted analyses suggesting a 20% to 30% reduction in mortality rates, consistently with other reports. [23][24][25][26] This reduction was observed among AF patients both with and without concomitant HF.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] However, ICDs are costly, have occasional complications early after implantation (e.g., infection), and may have later adverse outcomes including inappropriate shocks and device malfunction that lead, in some patients, to a diminished quality of life. 6 The currently recommended medications for heart failure with reduced ejection fraction, including angiotensin-converting-enzyme (ACE) inhibitors or angiotensin-receptor blockers, 7,8 beta-blockers, 9 and mineralocorticoid-receptor antagonists, 10 reduce the risk of sudden death. After the accrual of evidence from randomized, controlled trials, these drugs have increasingly been used in combination, with the latest guidelines recommending treatment with all three in most patients.…”
mentioning
confidence: 99%